2013
DOI: 10.1371/journal.pone.0066758
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Avenin-Like b Proteins in Bread Wheat (Triticum aestivum L.) Improves Dough Mixing Properties by Their Incorporation into Glutenin Polymers

Abstract: Avenin-like b proteins are a small family of wheat storage proteins, each containing 18 or 19 cysteine residues. The role of these proteins, with high numbers of cysteine residues, in determining the functional properties of wheat flour is unclear. In the present study, two transgenic lines of the bread wheat overexpressing avenin-like b gene were generated to investigate the effects of Avenin-like b proteins on dough mixing properties. Sodium dodecyl sulfate sedimentation (SDSS) test and Mixograph analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 53 publications
1
22
0
Order By: Relevance
“…In module 7 GSH showed strong associations with the expression of genes encoding avenin‐like proteins. GSH is a major reservoir of non‐protein reduced S in grains and can also contribute to protein polymerization and consequently affect baking performance (Rhazi et al ., ,b; Tea et al ., ; Zörb et al ., ), whereas the avenin‐like proteins are rich in Cys residues and are known to affect dough strength and resistance break down during the mixing of the dough (Clarke et al ., ; Ma et al ., ). Therefore, this tight relationship between GSH and avenin‐like transcripts is interesting and deserves further investigation.…”
Section: Resultsmentioning
confidence: 97%
“…In module 7 GSH showed strong associations with the expression of genes encoding avenin‐like proteins. GSH is a major reservoir of non‐protein reduced S in grains and can also contribute to protein polymerization and consequently affect baking performance (Rhazi et al ., ,b; Tea et al ., ; Zörb et al ., ), whereas the avenin‐like proteins are rich in Cys residues and are known to affect dough strength and resistance break down during the mixing of the dough (Clarke et al ., ; Ma et al ., ). Therefore, this tight relationship between GSH and avenin‐like transcripts is interesting and deserves further investigation.…”
Section: Resultsmentioning
confidence: 97%
“…For example, several endogenous wheat enzymes, proteases (Bleukx, Brijs, Torrekens, Van Leuven, & Delcour, 1998), endoxylanases (Cleemput, Hessing, van Oort, Deconynck, & Delcour, 1997;Cleemput, Van Laere, Hessing, Van Leuven, Torrekens, & Delcour, 1997), enzyme inhibitors, protease inhibitors (Stauffer, 1987) and xylanase inhibitors (Debyser, Derdelinckx, & Delcour, 1997) affect bread-making performance. Avenin-like proteins can influence dough rheological properties by sulfhydryl/disulphide crosslinks with gluten proteins (Ma, Li, Li, Liu, Liu, Li, et al, 2013). It is also reported that polymeric storage globulins are associated with low bread-making performance (MacRitchie, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…For example, HMW-glutenin x-and y-type subunits contain four to six cysteines, while α-gliadin and γ-gliadin have six to eight and eight to eleven cysteines, respectively ( Figure S4). Type a-, b-and c-avenin-like proteins (ALPs) have 14, 18-20, and 10-12 cysteine residues, respectively, and some ALPs have effects on dough quality, likely due to the number of cysteine residues for interaction with wheat storage proteins ( Figure S4) [49][50][51][52]. Here, PINB2 identified in the bread wheat genome of CS shares the same cysteine-rich backbone consisting of 10 residues as PINA, PINB, and GSP ( Figure S4).…”
Section: Genomic and Phylogenetic Analyses Of Pinb2 Genesmentioning
confidence: 99%